Repercussão geral no recurso extraordinário - Gonzalez, Anselmo Moreira (2011)
The work will presents the Institute of “repercussão geral”: a mandatory procedural prerequisite to the admissibility of extraordinary legal opened in Constitutional Amendment No. 45/2004. There will be a historical analysis in order to understand the influence of foreign law in the formation of the Brazilian judicial organization and also a detailed analysis of the organization of the constitutional law of our country before and after the release of the 1988 Constitution. Then, the work will talk about the crisis of multiple resources has been established in several countries that have adopted the system of civil law and the solutions found by some of these countries to solve the problem. Will be discussed hereinafter, the main measures adopted by Brazil to try to resolve the crisis of resources until reaching the issue of Constitutional Amendment nº. 45/2004 and the subsequent establishment of the institute object of this work. In a chapter devoted entirely to “repercussão geral”, the work will present its main procedural and constitutional aspects, such as the extraordinary appeal is prosecuted in Supreme Court and to what extent the picture of the overall effect influences the legal system as a whole and could solve the crisis of multiple resources. Further, the work will dedicate a special part to bring the statistical data collected by the Federal Supreme Court, making a picture of the impact to the overall impact on the flow of the extraordinary resources provided here. In the end, the conclusion will be discoursed on this important institute which has no doubt messing with the structure of the Brazilian judiciary, and that meant even if not itself an end to the so-called crisis of the judiciary undoubtedly represents a great tool so that one day it can be possible